Vertically Coupled Microring Laser Devices based on InP using BCB Wafer Bonding - Hamacher, M. (Institutional Knowledge at Singapore Management University, 2007)
In this paper, we present our approach on the realization of vertical coupling technology that has been verified for microlaser fabrication as well as for the realization of high Q resonators with 'loss-less' cavities based on InP. The concept is based on full wafer technology and provides the integration of an optical transparent passive bus waveguide vertically coupled to the active ring laser.